Etica della vulnerabilità, teoria e pratica della giustizia nell’opera di Concepción Arenal - Russo, Maria Teresa (B@belonline, 2020)
The bicentenary of the birth of Concepción Arenal (1820-1893) offers the opportunity to reflect on her work as an essayist, criminal lawyer and activist of civil and social rights. With her writings and her commitment, she anticipated many of the issues that would animate the political debate of the early decades of the twentieth century: the defense of women, criminal reform, child protection and the worker question. The article highlights the concern that Arenal had for the most vulnerable categories, in particular for women, convinced that justice is inseparable from charity and that education is the most effective leverage for an authentic development.